KARAKTERISTIK SENSORI MIE SAGU BERBASIS OLAHAN RUMPUT LAUT HASIL OPTIMASI KARAGENAN, CMC, DAN LAMA PENGERINGAN - Rahmawati, Rahmawati; Fadhilah, Nisrina; Haryanto, Bambang (Jurnal Teknologi Pangan dan Kesehatan (The Journal of Food Technology and Health), 2025)
Sago has health potential seen from its advantages over wheat, namely a low glycemic index (GI) and contains carbohydrates that are almost the same as wheat, however, the diversification of processed products is still limited. Processing sago into noodles will increase product diversification, but sago has the disadvantage of not containing gluten so that to produce good noodles, binders and stabilizers are needed, such as carrageenan and CMC. The aim of the study was to find the best formula of sago noodles from optimization: carrageenan; CMC and drying time with combined design. The upper and lower limits used for carrageenan 1%-0.5%; CMC 1.1%-0.6% and drying time 3.2-3.5 hours. Formula using Design Expert 13® application with combined design method D-optimal 16 formulas were tested. The best formula with desirability 0.746 was found in the formula of carrageenan 0.54%, CMC 1.06% and drying time 3.32 hours. Based on the results of the study, the hedonic color of sago dried noodles 3.67, the quality score of sago dried noodles 3.68, the hedonic texture of sago dried noodles 3.7, the quality score of sago dried noodles texture 3.69, the hedonic color of boiled sago noodles 3.68, the quality score of boiled sago noodles 3. 69, hedonic aroma of boiled sago noodles 3.71, quality score of boiled sago noodles aroma 3.59, hedonic texture of boiled sago noodles 3.73, quality score of boiled sago noodles texture 3.63, hedonic flavor of boiled sago noodles 3.72, quality score of boiled sago noodles flavor 3.71.